Пассивное согласование в измерительных цепях термоэлектрических датчиков - Луценко, В.Ю.; Жагров, А.С.; Оселедчик, Ю.С. (Технічна електродинаміка, 2012)
The analysis of electromagnetic processes of transformation of a low-power signal termo-EdS the thermocouples, occurring in the switching converter and the raising transformer is made. Expression for function of a gain which allows to estimate expediency of application of the switching converter or the raising transformer depending on resistance of the gauge is received, and also to define necessary for achievement of the maximum sensitivity of the measuring scheme value of factor of transformation.